Legal Challenges to Implementing the New Oil and Gas Law in Iraq - Shakir Hashim , Saif (South Asian Journal of Social Sciences and Humanities, 2025)
The Iraqi oil and gas law was not born of chance with the discovery of oil. Rather, it was a logical consequence of the historical development of oil and gas law and the obstacles it encountered, the most important of which was the sovereignty issue, which we addressed in the introduction to this research. The licensing method and the effectiveness of administrative oversight in granting these sensitive contracts were the basis for approval. The oil sector in Iraq is considered one of the primary economic resources that contribute significantly to the economy. The legal framework for oil extraction contracts is a pivotal element in ensuring national benefit. To regulate this vital sector, oil operations are managed in a legally and transparent manner. These contracts aim to define the relationship between the Iraqi government and local and international companies, ensuring the preservation of the state’s rights to its natural resources and providing an investment environment that encourages partnerships with international companies. This legal framework presents significant challenges, as it requires coordination between the various stakeholders, in addition to balancing economic and political interests. This is what we reviewed in our research by examining the shortcomings of the licensing method and the effectiveness of the administration’s oversight during the approval and granting of petroleum licenses.